Entre sentiment de responsabilité et aversion pour l’arbre : les bandes riveraines vues par les agriculteurs - Julie Ruiz; Aurélie Dumont; Marie-Pierre Maurice; Stéphane Campeau (VertigO)
In the Quebec context where regulatory compliance with riparian buffer is controversial and where the development of widened riparian buffer remains difficult, this research offers an in-depth analysis of farmers' attitudes. It examines the affective, cognitive and behavioral components of attitudes to question both regulatory compliance with riparian buffer and the interest of producers for several types of wide riparian buffers : cultivated with hay, with shrubs, with trees. It is based on semi-structured interviews with 26 producers localized in an intensive agricultural area in the south of the province. The analysis first shows that the notion of riparian buffer refers to positive feelings for some farmers and negative for others, although many of their environmental benefits are known. Knowing the benefits of riparian buffer is therefore not the sole factor influencing behavior. Regulated riparian buffers appear to be increasingly accepted mainly as a personal, moral and social responsibility, even if they continue to be rejected by some farmers. Wide riparian buffer only seem to be possible without trees and in places where producers are aware of particular problems that affect soil conservation. Given the role of social norms in the attitudes of farmers, the analysis suggests to incorporate farmers within a local group learning situation with peers to improve the establishment of riparian buffer strips.